Sex differences in metabolically healthy and metabolically unhealthy obesity among Chinese children and adolescents - Cai, Shan; Dang, Jiajia; Zhong, Panliang; Ma, Ning; Liu, Yunfei; Shi, Di; Zou, Zhiyong; Dong, Yanhui; Ma, Jun; Song, Yi (Frontiers in Endocrinology, 2022)
Objectives: To analyze sex differences in the prevalences of obesity phenotypes and their risk factors among children and adolescents aged 7-18 years in China. Methods: We enrolled 15,114 children and adolescents aged 7-18 years into the final analysis. Obesity phenotypes were classified by BMI and metabolic status as metabolically healthy or unhealthy obesity. Besides, we collected four aspects of possible influencing factors on obesity phenotypes through questionnaires, including demographic, parental, early life, and lifestyle indicators. Multinomial logistic regression analysis in a generalized linear mixed model (GLMM) was selected to estimate the odds ratio (OR) and 95% confidence interval (95% CI) for identifying risk factors, and control the cluster effects of schools additionally. More importantly, the interaction terms of sex and each indicator were established to demonstrate the sex differences. Results: The prevalences of metabolically healthy obesity (MHO), metabolically unhealthy obesity (MUO), metabolically healthy overweight and obesity (MHOO), and metabolically unhealthy overweight and obesity (MUOO) were 3.5%, 5.6%, 11.1%, and 13.0% respectively, with higher prevalences in boys (5.3% vs. 1.6%, 7.9% vs. 3.1%, 14.3% vs. 7.7%, 15.6% vs. 10.1%). In addition, younger ages, single children, parental smoking, parental history of diseases (overweight, hypertension, diabetes), caesarean, premature and delayed delivery time, high birth weight, insufficient sleep time, and excessive screen time were considered as important risk factors of MHO and MUO among children and adolescents (p < 0.05). More notably, boys were at higher risks of MUO when they were single children, while girls were more sensitive to MUO with parental smoking, premature delivery, high birth weight, and excessive screen time (pinteraction < 0.05). Conclusions: MHO and MUO are becoming prevalent among Chinese children and adolescents. Significant sex differences in the prevalences of obesity phenotypes as well as their environmental and genetic risk factors implicated it might be necessary to manage obesity phenotypes problems from a sex perspective.